2017
DOI: 10.20344/amp.8202
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of 39-Item Parkinson’s Disease Questionnaire and Parkinson’s Disease Quality of Life Questionnaire

Abstract: Introduction: Parkinson’s disease has a significant impact in quality of life, which can be assessed with 39-item Parkinson’s Disease Questionnaire and Parkinson’s Disease Quality of Life Questionnaire. This study aimed to evaluate the reliability and validity of these scales in Portuguese patients.Material and Methods: Reliability was assessed through internal consistency (Cronbach’s alpha) and reproducibility (intraclass correlation coefficient). Regarding construct validity, we performed one-way analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The Cronbach's alpha coefficients in the present study (range of 0.69 to 0.92) were similar to those found by Peto et al [18] in the original validation study and to those of the original British version [19]. They were also similar to those obtained in most translations [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and validation studies [20, 26-28, 30, 31]. In this study, the Cronbach's alpha coefficient for the social support subtest was < 0.70, suggesting that this dimension may not provide accurate data.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The Cronbach's alpha coefficients in the present study (range of 0.69 to 0.92) were similar to those found by Peto et al [18] in the original validation study and to those of the original British version [19]. They were also similar to those obtained in most translations [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and validation studies [20, 26-28, 30, 31]. In this study, the Cronbach's alpha coefficient for the social support subtest was < 0.70, suggesting that this dimension may not provide accurate data.…”
Section: Discussionsupporting
confidence: 89%
“…Among the eight dimensions of the PDQ-39, Spearman's rank correlation coefficients for the total score of the SF-36 were significant [50]. Most previous validation studies of the PDQ-39 in other cultural settings used a variety of rating scales and classifications to assess construct validity [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. All these studies found statistically significant correlations between disease severity and some of the PDQ-39 domains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each item ranges from 0 (never) to 4 (always). A summary index of eight domain scores ranges from 0 to 100, with higher scores representing worse health-related quality of life 37 38. The data collected are depicted in table 2.…”
Section: Methodsmentioning
confidence: 99%